3-Dimensionally ordered macroporous PEDOT ion-exchange resins prepared by vapor phase polymerization for triggered drug delivery: Fabrication and characterization. (10th April 2018) - Yasin, M. Naveed; Brooke, Robert K.; Rudd, Sam; Chan, Andrew; Chen, Wan-Ting; Waterhouse, Geoffrey I.N.; Evans, Drew; Rupenthal, Ilva D.; Svirskis, Darren
Abstract: This paper reports a simple fabrication strategy towards 3-dimensionally ordered macroporous (3DOM) poly(3, 4-ethylenedioxythiophene) (PEDOT) thin films via vapor phase polymerization (VPP) coupled with colloidal crystal templating. PEDOT was synthesized by VPP over a colloidal crystal thin film composed of monodisperse polystyrene colloids functionalized with a Fe(III) tosylate catalyst, after which the polystyrene template was selectively removed. The resulting 3DOM PEDOT films comprised a face-centered cubic array of 280–290 nm spherical macropores in a PEDOT matrix, around 5–6 μm thick. Cyclic voltammetry (CV) was used to probe electrochemistry and highlighted the merits of the fabrication strategy introduced here; the 3DOM PEDOT films exhibit a 2.9-fold increase in electrochemically available surface area compared to the non-templated PEDOT films. As a demonstration of functionality, ion-exchange of the dopant tosylate for the anionic drug dexamethasone phosphate (dexP ˉ ) was explored. Loading by passive ion exchange was three-fold higher for 3DOM PEDOT compared with non-templated PEDOT. Notably, CV-driven ion exchange was more efficient to load drug into the polymer than passive ion exchange, and occurred to similar extents for both non-templated PEDOT and 3DOM PEDOT structures. Following loading, minimal dexPˉ release was observed in the absence of an electrical stimulus, while dexPˉ release was triggered upon application of a suitable electrical stimulus. 3DOM PEDOT prepared by VPP thus represents a promising material for use as an ion exchange resin with drug loading achieved subsequent to polymerization and electrically triggered drug release demonstrated. Graphical abstract: Image 1 Highlights: Highly ordered macroporous PEDOT synthesized via vapor phase polymerization. Macropores impart a near 3 fold increase in electrochemically accessible surface area over non-templated PEDOT. CV-driven ion exchange can be used to enhance drug loading into PEDOT. Dexamethasone release was triggered upon application of an electrical stimulus.